2022
DOI: 10.3389/fncel.2022.917884
|View full text |Cite
|
Sign up to set email alerts
|

Neu1 Is Released From Activated Microglia, Stimulating Microglial Phagocytosis and Sensitizing Neurons to Glutamate

Abstract: Neuraminidase 1 (Neu1) hydrolyses terminal sialic acid residues from glycoproteins and glycolipids, and is normally located in lysosomes, but can be released onto the surface of activated myeloid cells and microglia. We report that endotoxin/lipopolysaccharide-activated microglia released Neu1 into culture medium, and knockdown of Neu1 in microglia reduced both Neu1 protein and neuraminidase activity in the culture medium. Release of Neu1 was reduced by inhibitors of lysosomal exocytosis, and accompanied by ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Therefore, NEU3 KO cells are still able to secrete inflammatory signals. TNFα secretion in both cell lines was inhibited by the pan-sialidase inhibitor deoxy-2,3-anhydroneuraminic acid (DANA), consistent with previous observations with Neu1. , Given that the BV-2 microglia are still capable of secreting inflammatory molecules, Neu3-mediated autodesialylation is not a prerequisite for inflammatory activity in the manner as has been reported for Neu1 . Moreover, these data implicate Neu3 as the secreted sialidase, rather than an upstream component.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, NEU3 KO cells are still able to secrete inflammatory signals. TNFα secretion in both cell lines was inhibited by the pan-sialidase inhibitor deoxy-2,3-anhydroneuraminic acid (DANA), consistent with previous observations with Neu1. , Given that the BV-2 microglia are still capable of secreting inflammatory molecules, Neu3-mediated autodesialylation is not a prerequisite for inflammatory activity in the manner as has been reported for Neu1 . Moreover, these data implicate Neu3 as the secreted sialidase, rather than an upstream component.…”
Section: Resultssupporting
confidence: 87%
“…As prior studies have implicated Neu1 translocation and desialylation in cis as a critical component of microglial activation, ,, we sought to determine whether the loss of secreted sialidase activity in NEU3 KO BV-2 cells was a consequence of impaired inflammatory activity. We observed that NEU3 KO cells had impaired autodesialylation in response to LPS treatment compared to WT as measured by periodate labeling of sialic acids ( p = 0.51 and = 0.038, respectively), but that both WT and NEU3 KO cells upregulated TNFα to similar levels in (WT, p = 0.002; NEU3 KO, p = 0.02) (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, sialic acid often binds galactose residues on cell surface phagocytic receptors (e.g., MerTK) and phagocytic targets as does Gal-3, thus impeding phagocytosis by blocking Gal-3 binding/crosslinking MerTK and targets (reviewed in Puigdellivol et al, 2020). Nomura et al (2017) and Allendorf and Brown (2022) showed in this context that the LPS-treated microglia increased the release of Neuraminidase 1 (Neu1), which through desialylation exposed galactose residues on MerTK and targets, thus leading to augmented phagocytosis by enabling Gal-3 binding and so crosslinking MerTK and targets. Taken altogether, efficient MerTK-mediated phagocytosis of Gal-3-opsonized targets depended on inflammatory stimuli activating microglia to upregulate MerTK expression and further increase Gal-3 and neuraminidase secretion.…”
Section: Microgliamentioning
confidence: 99%